Классные часы в средней школе: практическое пособие / Е. П. Сгибнева - Сгибнева Елена Петровна (Методика, 2005)
Экземпляры: аб. (2005) / Инвентарный номер: 48769 / Цена: / Сис.шифр: 74.200.5 / Авт.знак: С 26 / ГРНТИ: 14.25.05 / ББК: 74.200.5